2016
DOI: 10.1007/s11739-016-1406-x
|View full text |Cite
|
Sign up to set email alerts
|

Pocket ultrasound device as a complement to physical examination for ascites evaluation and guided paracentesis

Abstract: The pocket ultrasound device (PUD) is a new tool that may be of use in the early detection of ascites. Abdominal ultrasound-guided paracentesis has been reported to decrease the rate of complications due to the procedure, but must be performed in a healthcare setting; this new tool may be a useful on an ambulatory basis. The aim of this study was to determine the diagnostic usefulness of the PUD in the diagnosis of ascites and the safety of guided paracentesis. We conducted a retrospective study that included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…In 216 trauma patients, HHUSD FAST-scanning had an NPV of 99.5 %, signifying that HHUSDs could be used to rule out free abdominal fluid [12]. Concordantly, in patients clinically suspected of ascites, HHUSDs successfully confirmed the diagnosis in 96 % of cases, while the diagnosis was only missed in mild cases as assessed by conventional ultrasound or computed tomography (CT) [14]. In the same study HHUSD-guided paracentesis of ascites was feasible in 38 of 40 patients, with no severe complications.…”
Section: Abdominal Handheld Ultrasoundmentioning
confidence: 96%
“…In 216 trauma patients, HHUSD FAST-scanning had an NPV of 99.5 %, signifying that HHUSDs could be used to rule out free abdominal fluid [12]. Concordantly, in patients clinically suspected of ascites, HHUSDs successfully confirmed the diagnosis in 96 % of cases, while the diagnosis was only missed in mild cases as assessed by conventional ultrasound or computed tomography (CT) [14]. In the same study HHUSD-guided paracentesis of ascites was feasible in 38 of 40 patients, with no severe complications.…”
Section: Abdominal Handheld Ultrasoundmentioning
confidence: 96%
“…Two articles not included in this review showed good overall agreement for detecting B-lines in patients with heart failure, as well as for visualising the diaphragm [37,38]. Some articles concerning hand-held ultrasound in abdominal pathology were not limited to comparing hand-held ultrasound devices with a specific high-end system [29,39,40,41], but were compared with other diagnostic measures, such as physical examination, CT and MRI, as well as US and were not included in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal POCUS can be used to readily identify a variety of pathological states including ascites, cholecystitis, cholelithiasis, nephrolithiasis, hydronephrosis, and abdominal aortic aneurysm. [54][55][56] Its use has been shown to improve diagnostic accuracy and reduce ER length of stay. 55,56 While abdominal POCUS is incorporated into standardized examinations such as the Focused Assessment with Sonography for Trauma (FAST), these examinations are subject to variability based on user experience and have not been extensively validated as tools to assess competency.…”
Section: Abdominal Pocusmentioning
confidence: 99%